Ambulatory blood pressure monitoring in children undergoing polysomnography. (3rd February 2021) - DelRosso, Lourdes M.; Chan, Jeremy; Ruth, Chris; Powell, Weston T.; Arp, Michelle; Hanevold, Coral; Ferri, Raffaele
Abstract: Ambulatory blood pressure monitoring (ABPM) is recommended for the diagnosis of hypertension in children at high risk, such as children with obesity or obstructive sleep apnea (OSA). Nocturnal hypertension is highly predictive of cardiovascular outcomes. ABPM allows for early detection of nocturnal hypertension in children. Although OSA is the most common sleep disorder associated with hypertension, studies have also shown an increase in cardiovascular risk in adult patients with other sleep disorders; therefore, there is an imperative need to provide early diagnosis in children at high risk. In the present study, we evaluated the feasibility of using ABPM during polysomnography (PSG) in children referred for sleep disordered breathing to the Seattle Children's Hospital Sleep Disorders Center. A total of 41 children aged 7–18 years were included in this study. The ABPM monitor was worn for a mean ( SD ) of 10.2 (1.5) hr. No significant changes were seen in PSG parameters when ABPM was co‐performed with PSG, including sleep efficiency and arousals. In total, 12 of the 41 patients were identified as having nocturnal hypertension. Our study is important in that it shows that concomitant use of ABPM during PSG can aid in the early identification of nocturnal hypertension in this population.